Management pathways for erectile dysfunction in primary care. (2nd January 2021) - Steggall, Martin; Mohammed, Imran; Jones, Keryn; Shanahan, Anthony; Ellul, Thomas; Bullock, Nicholas; Brown, Gareth
Abstract : Erectile dysfunction is a common problem in primary care. Martin Steggall and colleagues discuss what needs to be assessed and the treatment options available Erectile dysfunction (ED) is defined as the inability of a man to get and maintain an erection that is sufficient for sexual intercourse, and is a common problem. ED commonly has a profound negative impact on quality of life in the patient and his partner, which can result in changes to sexual self-confidence. This article outlines strategies for identifying and managing ED in primary care, outlining what needs to be assessed and the various treatment options available to manage the condition.